2011
DOI: 10.1088/0268-1242/26/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

Combined scheme of UV/ozone and HMDS treatment on a gate insulator for performance improvement of a low-temperature-processed bottom-contact OTFT

Abstract: This study investigates the performance improvement of a pentacene-based OTFT (organic thin-film transistor) by the combined scheme of UV/ozone cleaning and hexamethyldisilazane coating on a gate insulator. Because the surface energy and the trap state density of the gate insulator were effectively improved, the combined scheme can significantly advance the performances of the OTFT, compared to those of the samples without any surface treatments, such that the field-effect mobility was dramatically increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…OH‐groups act as electron traps, which have a great influence on the switching on behaviour of an OTFT, shifting V on in the positive direction. The surface area density of OH‐groups on a SiO 2 ‐dielectric is difficult to control, highly sensitive to various surface treatments , and thus also strongly depends on the humidity during sample preparation, the timespan between preparation steps, etc. Starting from the individual V on for each device, the evolution of V on with coverage is, however, very similar for all devices with SiO 2 as gate dielectric, corresponding to a voltage shift of D V on,sat ∼ 15–20 V. A similar shift with similar saturation value D V th,sat ∼ 20 V is observed for the threshold voltage in devices with pure SiO 2 dielectric (compare V on SiO 2 and V th SiO 2 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OH‐groups act as electron traps, which have a great influence on the switching on behaviour of an OTFT, shifting V on in the positive direction. The surface area density of OH‐groups on a SiO 2 ‐dielectric is difficult to control, highly sensitive to various surface treatments , and thus also strongly depends on the humidity during sample preparation, the timespan between preparation steps, etc. Starting from the individual V on for each device, the evolution of V on with coverage is, however, very similar for all devices with SiO 2 as gate dielectric, corresponding to a voltage shift of D V on,sat ∼ 15–20 V. A similar shift with similar saturation value D V th,sat ∼ 20 V is observed for the threshold voltage in devices with pure SiO 2 dielectric (compare V on SiO 2 and V th SiO 2 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that UV ozone removes the contaminants from the SiO 2 surface, leaving unstable dangling bonds that become terminated with hydroxyl (-OH) groups, making the SiO 2 surface more hydrophilic and thus susceptible to adsorption of contaminants. [15][16][17] This mechanism also explains the increased effectiveness of the cleaning procedure that includes both the UV ozone treatment and the HCl bath. By following the UV ozone treatment with an HCl bath, Cl ions replace the hydroxyl groups, leaving the surface hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this process is the growth of the SiOx on the surface of QDs as shown in Figure 1a. HMDS is widely used in cleaning processes that oxidize around impurities on the semiconductor wafer surface with chemical stability and then remove them through etch [22,23]. With this in mind, it is intended to improve the properties by oxidation on the surface of QDs.…”
Section: Introduction Of Hmds For Qd Improvementmentioning
confidence: 99%